Analisis Pelaksanaan Bimbingan Belajar dalam Mengatasi Kesulitan Belajar Siswa - Rozak, Abdul; Fathurrochman, Irwan; Ristianti, Dina Hajja (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to determine the description of the planning of the Counseling Guidance program especially PKO Services in the field of Guidance and to find out the extent of the implementation of Tutoring by the Supervising teacher in overcoming student learning difficulties at Simpang Semambang High School. The subjects of this study were the Supervising Teacher, Principal and students. This type of research is field research, with a qualitative descriptive approach. Data collection techniques by observation, documentation, interviews and KPMP data distribution. Data analysis techniques using qualitative descriptive analysis. The results of the research and data analysis concluded that the Guidance and Counseling service program at Simpang Semambang High School had been planned and made according to the needs of the school and the existing guidelines. The fact is the implementation of tutoring in Simpang Semambang State High School is sometimes not fully able to solve every problem of student learning difficulties that occur as a result of the service process or guidance that is carried out with minimal intensity and minimal continuity, it could be from other factors that influence it. Services are carried out in a classical format, namely in the classroom, while service material is only in the form of advice and motivation, while services in the field of tutoring are still minimal. Keywords: Implementation of Tutoring Program, Learning Difficulty